The System of Political Parties in India (Czech Journal of International Relations, 1999)
The Indian party system is a most unusual phenomenon, for at least two reasons. First, its form differs totally from the so-called Duverger laws under which a country which in elections to the lower chamber of its parliament, uses the one-round relative plurality system, should have a bipartisan regime. But the form of the party system in India is multi-partisanism. The second reason why the author turns his attention to the Indian party system is the fact that the party regime in question has changed from a system of one predominant party (the Indian National Congress) to a classic multi-party system; this occurred essentially in the early 1980s when a new relevant political subject – the Indian People's Party (BJP) – came to the fore and took its place next to the traditional centre-left Indian National Congress. First of all, one has to understand the complex nature of the Indian party spectrum where, on the basis of clear criteria, only 42 of the total number of 654 parties are officially recognized and registered; of these, seven are regarded as national parties (that is all-Indian, federal), and thirty-five as state parties (i.e. regional).The author asks himself two fundamental questions in the article: What is the reason for the multi-party system in India? What polarity does this Indian multi-party regime reveal? India is a multi-ethnic and multi-cultural formation, and consequently the variety of parties is nothing unusual. Each of the twenty-five states making up the Indian Union has in most cases a population of different nationalities and ethnic origin, the interests of this population are presented by their own regional (in the Indian context, state) parties. But precisely because of the electoral system to the lower chamber of the federal parliament (the People's parliament), these small political subjects have become immensely significant elements. If they are successful in the elections, the INC and the BJP are directly dependent on these small regional parties which can either support INC or BJP minority governments, or become part of government coalitions where the INC or the BJP are the nucleus. As regards the second question, the author tends to the opinion that the current Indian extreme and fragmented multi-partisanship must be regarded as bipolar (the INC and the BJP are two poles), since the potential third pole – the United Front (UF) – (an expedient block of a number of very different parties) appears to be most unstable. The UF turns into the relevant third force only during an election campaign or when it succeeds in becoming the ruling party (there was a UF minority government in 1996-1997, supported by the Congress Party). When the UF is an opposition group (as after the 1998 elections) it is a subject that becomes entirely inconsistent. That is why we cannot regard it as a firm third pole in the Indian multi-party system.